How are new collective models transforming support for smallholder farmers? Empirical evidence from thematic and sentiment content analysis - Rajiv B. Kale; Pooja A. Dangi; Vinayak Nikam; Kiran Khandagale; Shailendra S. Gadge; Vijay Mahajan (Frontiers in Sustainable Food Systems)
Collective farmer models represent an important approach for smallholders to engage in agricultural activities collaboratively, fostering sustainable economic development, particularly in the context of India. The increasing frequency of published research articles on collective models highlights their significance in addressing various challenges faced by smallholder farmers in India and globally. This study is guided by three primary research questions: first, to identify trends in publications related to collective models; second, to measure the sentiments associated with the identified themes within this literature; and third, to uncover the potential of various collective models in meeting the needs of smallholder farmers, with a particular focus on India. The study analyzed research articles published from 2000 to 2024, focusing on the frequency of appearance and the content related to the functions of farm collectives. Utilizing a descriptive quantitative approach, this research employs content analysis to gather primary data from 4,382 research articles. The NVivo 15 tool is used to analyze the data, identifying key themes, functions, and support agencies as units of analysis. Through this comprehensive analysis, the study seeks to elucidate the emergence of collective models and their potential to address critical agricultural issues faced by smallholder farmers, particularly in India. The research underscores the evolving trends of farmers’ collectives, transitioning from cooperatives to contemporary Farmer Producer Companies in response to emerging needs. The findings from the global literature provide valuable insights for enhancing the development of collective models in India, where such initiatives can play a transformative role in addressing the challenges of smallholder farmers.